EFFECT OF CEFOTAXIME ON ESCHERICHIA COLI ISOLATED FROM URINARY TRACT INFECTION - Maher Ali Abdul Hussein Shaaban; Muqtada Hamid Abd Yasser; Zahraa salim saed Abed; Abdulaziz Younis Mahmood Ahmed (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study aims to detect the effect of cefotaxime antibiotic on Escherichia coli bacteria isolated from urinary tract infections. 27 clinical samples were collected from the urine of women with urinary tract infections caused by Escherichia coli bacteria under the supervision of a specialist doctor at Al-Rifai General Hospital in Al-Rifai District / Dhi Qar Governorate. Escherichia coli bacteria have been diagnosed by conventional methods, which have confirmed infection with Escherichia coli. A drug susceptibility test was conducted for bacterial isolates of E. coli to the antibiotic cefotaxime from 27 female patients believed to have UTIs. The Statistical package for the social sciences (SPSS) system was adopted in this study for the purpose of statistical analysis, which express the negative or positive effect of the antibiotic cefotaxime on female patient samples, according to the target age groups. In the study. If we conclude from the foregoing from the current study that the rate of resistance of E. coli bacteria to the antibiotic cefotaxime has reached 70%, and this is consistent with the study of researcher Harran (2012), which confirmed the high and large resistance of E. coli to the antibiotic cefotaxime of the group of third- generation antibiotics The cephalosporins group, and the rate of resistance to the previous antibiotic was 76.6%. The results of this study also coincided with the results of the researcher’s study SURESH (2016) in India, where the percentage of E. coli resistance to the antibiotic cefotaxime was 100%. This study was also compatible with the researcher’s study HEGAZY (2018), which demonstrated the resistance of E. coli isolates to the antibiotic cefotaxime by 74.4%, and the reason for the aforementioned results of the current study and studies compatible with it is due to the ability of E. coli to resist the antibiotic cefotaxime due to its possession of efficient flow pumps in the elimination of the antibiotic The previous bio outside the cell and the removal of the effect of this antibiotic, and thus the existence of the natural efflux pumps outside the cell (Efflux pums), and perhaps one of the most important efflux systems possessed by E. coli is the AcrAB-ToIC system of the RND family, which is the most common efflux system in E. coli, Through which you can change the permeability of the outer membrane of the germ cell. coli bacteria have many mechanisms to resist beta-lactam antibiotics, as they work to produce beta-lactamase enzymes stationed in the proplasmic vacuole, and these enzymes attack beta-lactam antibiotics before they reach the target, and the bacterial cell works to reduce its permeability to prevent the entry of antibiotics and thus inhibit their action, and it is possible The bacterial cell acts as a pump driving the antibiotic beyond its borders, but the most common mechanism is its production of beta-lactamase enzymes and its importance comes through its ability to open the beta-lactam ring for both penicillins and cephalosporins (Frere et al., 2015; Bush, 2015; Chambers et al., 2005). Several studies indicate that if E. coli bacteria show resistance to ceftriaxone, ceftazidime, azotronam, and cefotaxime, they are considered broad-spectrum to resist many beta-lactams (penicillins, cephalosporins, and monobactams) due to the production of extended spectrum β-lactamases (ESBLs). ] making the treatment menu for patients with UTIs limited